Predictores de la composición corporal de estudiantes universitarios de ciencias de la salud - Monteza Rojas, Nancy Jhaneth (2025)
The present investigation aimed to determine the predictors of the body composition of Health Sciences students. Its approach was quantitative with a descriptive, correlational and predictive design. The sample was made up of 445 Health Sciences students who are in the first and second year of studies and was determined by proportional allocation and selected by stratified sampling. The data were processed using SPSS version 26, to identify the predictor variables, the analysis of variance was applied to contrast the difference in means and linear regression analysis by successive stages. Among the results, it was determined that the average age was 19.9±3.35 years. According to bioimpedance, only half of the students had a healthy body fat range (50.8%), 12.1% were overweight and 9.4% were obese. When comparing the means of body composition measurements according to sex, significant statistical differences were found in the values of fat mass, muscle mass, body water, bone mass, metabolic age and visceral fat (p<0.001).